As mídias nos oceanos da escola: diálogos interdisciplinares - Silva, Luciane Cristina (2020)
Nowadays, digital media occupy an increasingly prominent place and enable new forms of communication and interactivity, contributing to the establishment of a new educational reality, with multiple functionalities, being more and more present in the school routine, being able to promote access to new ones wisdoms and knowledge, especially through the expansion of the internet. In this premise, the dissertation presents results arising from a master's research, which had as an object of joint research with teachers moments of studies and knowledge production through continuing teacher education, which, as yet, also included students and educational agents. Thus, through an extension project and a study group, about the media theme, entitled: The media as a cultural artifact and its contributions to teaching, the research was being woven. The project was born from the scientific investigation of this theme and observation empirical of the school routine, and also of the conflicts over the use of media instruments as part of its methodological collection. This dissertation presents, through an action research and in the light of Cultural Studies, the dialogue with teachers, students and educational agents of a Basic Education school in Foz do Iguaçu about the insertion of the media in the its pedagogical practice, contrary to training limited to purely instructional practice. Considering the panorama that training as an interdisciplinary experience is fundamental for changing attitudes in the field of work, the research aims to study the media as a cultural artifact, and how it can be appropriated by education agents, collectively creating methodological strategies when using media resources to produce knowledge. As a result, it reaffirms the importance of guiding the theme, especially at school, as well as initial and continuing education that, in context, is a real practice, expanding the debate on the use of media in the classroom as an artifact that produces culture and scientific knowledge.